Microbial Pattern in Amniotic Fluid from Women with Premature Rupture of Membranes and Meconium-Stained Fluid - Fauna Herawati; Patricia Valery Rahaded; Ruddy Hartono; Rika Yulia (Pharmaceuticals, 2024)
Intra-amniotic infection (IAI), also known as chorioamnionitis, is a major cause of maternal and neonatal infection that occurs during pregnancy, labor and delivery, or in the postpartum period. Conditions such as meconium-stained amniotic fluid (MSAF) and premature rupture of membranes (PROMs) are recognized risk factors for amniotic fluid infection. This study identifies the microbial patterns in the amniotic fluid of women with PROMs and MSAF to determine the presence and types of bacterial growth. It also identifies trends in antibiotic use through descriptive statistics. Conducted as a descriptive observational study with prospective data collection, this research included maternal patients with PROMs lasting more than 12 h and those with MSAF, along with their infants. Of 30 cultured amniotic fluid samples, bacterial growth was observed in 13 cases, with Escherichia coli being the most prevalent (40%). Infants born with PROMs accompanied by MSAF were 5.5 days, significantly longer than those born with PROMs alone (3.19 days) or MSAF alone (3.91 days), with a significant difference between groups (p = 0.003). In addition, Escherichia coli isolates in this study are resistant to ceftriaxone, a third-generation cephalosporin antibiotic. Understanding these microbial patterns is critical for guiding clinical decisions, particularly in managing the risk of infection in pregnant women with PROMs and MSAF and ensuring better outcomes for both mothers and newborns.